Transponder Aggregator for CDC-ROADM Nodes Supporting S-U Bands and 32/64-WDM Ports - Keita Yamaguchi; Kenya Suzuki; Osamu Moriwaki (IEEE Photonics Journal)
In response to the rapid growth in traffic, the throughput and handling unit size of optical network nodes have been increasing at a rate of approximately ten times per decade. To achieve such high node throughputs, it is important to expand the wavelength bandwidth and support more WDM fibers. Therefore, the transponder aggregator (TPA) that provides the colorless, directionless, and contentionless (CDC) function of the network node also needs to respond to these changes. As a TPA suitable for such ultra-high throughput reconfigurable optical add/drop multiplexing (ROADM) nodes, we propose a multicast switch (MCS) that consists of 1 × N splitters and M × 1 switches facing each other and utilizes a silica-based planar lightwave circuit (PLC) platform. The CDC-ROADM nodes have a trade-off between the number of connected WDM fibers and the number of transponders that can be accommodated by a single TPA. Therefore, increasing the WDM fibers results in a decrease in the transponders that can be accommodated by a single MCS, but at the same time reduces the splitting loss in that switch. As a result, the number of optical amplifiers used for add/drop functions can be reduced. In addition, because the handling unit is larger, the increase in the number of required MCS units is limited, and highly integrated PLC-based MCSs become practical. In this paper, we demonstrate MCSs supporting 300-nm bandwidth and 32- and 64-degree nodes for the first time ever. The insertion loss of the prototype was less than 8.0 dB in all paths, including connections with common single-mode fiber, and the extinction ratio was greater than 40 dB.